Preface: 6th International Symposium on Economic Development and Management Innovation (EDMI 2024) - Chen, Yuanyuan; Ali, Hesham H. (Transactions on Economics, Business and Management Research, 2024)
This proceeding includes original and peer-reviewed research papers from the 6th International Symposium on Economic Development and Management Innovation (EDMI 2024), held in New York, United States during May 25-26, 2024.The aim of EDMI 2024 is to provide a platform for accountants, financial industry practitioners, scholars, managers and graduate students from different cultural backgrounds to present and discuss research, developments and innovations in all fields of Economic Development and Management Innovation. It provides opportunities for the delegates to exchange new ideas and application experiences, to establish business or research relations and to find global partners for future collaboration.EDMI 2024 received 93 manuscripts. By submitting a paper to this EDMI, the authors agreed to the review process and understood that papers undergo a peer-review process. Manuscripts were reviewed by appropriately qualified experts in the field selected by the Conference Committee, who gave detailed comments and-if the submission was accepted the authors would submit a revised version that considered this feedback. All papers were reviewed using a double-blind review process: authors declared their names and affiliations in the manuscript for the reviewers to see, but reviewers did not know each other’s identities, nor did the authors receive information about who had reviewed their manuscript. The Committees of EDMI 2024 invested great efforts in reviewing the papers submitted to the conference and organizing the sessions to enable the participants to gain maximum benefit.With our warmest regards,Yuanyuan ChenHesham H. AliConference Organizing Committee